The love letter - Pillsbury, Sarah; Chan, Peter Ho-Sun (USA: Dreamworks Home Entertainment [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 2000)
In the sleepy New England town of Loblolly By The Sea, a letter has arrived that is going to wake things up. It is a love-letter-ardent, sensual...and unsigned. As the letter falls into different hands, residents of the small town start to eye one another with renewed interest-wondering who it's for and who it's from
Executive producer, Beau Flynn, Stefan Simchowitz ; editor, Jacqueline, Cambas
Cast: Kate Capshaw, Blythe Danner, Ellen DeGeneres, Geraldine McEwan, Julianne Nicholson, Tom Selleck
Keywords: Comedy films; Love in motion pictures